ANALYSIS OF INFLUENCE OF PRICE, SERVICE QUALITY, BRAND IMAGE TO CUSTOMERS’ PURCHASE DECISION OF KOREAN MARINE TRANSPORT CO., LTD. ( A Case Study at PT. Samudera Indonesia Tbk. Semarang ) - Dwi - Rachmawati; Siti Nur Barokah; M Nahar (JOBS (Jurnal Of Business Studies), 2017)
The competition among shipping company is strict. The objective of this research is to analyze the influence of price, service quality, and brand image to customers’ purchase decision of Korean Marine Transport Co., Ltd. at PT. Samudera Indonesia Tbk. Semarang. This research used a multiple linear regression analysis. The primary data used in this research is collected from questionnaire. The amounts of the respondents are 56 who are customers of PT Korean Marine Transport Co., Ltd, at PT. Samudera Indonesia Tbk. Semarang. The calculation of multiple linier regressions which is carried out by SPSS 20 showed that price, service quality, and brand image variables have significant positive influenced on purchase decision in partially and simultaneously and the most dominant variable is service quality. The contribution of price, service quality, and brand image to purchase decision is 60.2% while 39.8% are influenced by other variables that were not described in this research.